2014
DOI: 10.1186/s12870-014-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptome analysis reveals insight into monosymmetric corolla development of the crucifer Iberis amara

Abstract: BackgroundIn the co-evolution between insects and plants, the establishment of floral monosymmetry was an important step in angiosperm development as it facilitated the interaction with insect pollinators and, by that, likely enhanced angiosperm diversification. In Antirrhinum majus, the TCP transcription factor CYCLOIDEA is the molecular key regulator driving the formation of floral monosymmetry. Although most Brassicaceae form a polysymmetric corolla, six genera develop monosymmetric flowers with two petal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Iberis amara in Brassicaceae has previously been used as a model species to understand the evolution of monosymmetric petals ( Busch et al 2014 ), in this paper, we report how I. amara evolved to produce cucurbitacins, a new chemical defense in the Brassicaceae for insect herbivores like Pieris rapae and Phyllotreta nemorum , which otherwise feed on many brassicaceous species ( Nielsen et al 1977 ; Sachdev-Gupta et al 1993 ). We elucidated the first three committed steps of the cucurbitacin biosynthesis in I. amara , and showed that the cucurbitacin pathway in this species has evolved independently to the corresponding pathway in cucurbitaceous species.…”
Section: Discussionmentioning
confidence: 92%
“…Iberis amara in Brassicaceae has previously been used as a model species to understand the evolution of monosymmetric petals ( Busch et al 2014 ), in this paper, we report how I. amara evolved to produce cucurbitacins, a new chemical defense in the Brassicaceae for insect herbivores like Pieris rapae and Phyllotreta nemorum , which otherwise feed on many brassicaceous species ( Nielsen et al 1977 ; Sachdev-Gupta et al 1993 ). We elucidated the first three committed steps of the cucurbitacin biosynthesis in I. amara , and showed that the cucurbitacin pathway in this species has evolved independently to the corresponding pathway in cucurbitaceous species.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, GO terms within fruits and between species are similar (Fig 3 and S1 Fig), as expected, because all sections and replicates are from developing fruit with shared components (e.g., ovary wall, septum). Additionally, GO analyses of top terms do not usually vary between closely related species [64,65]. However, despite similarities in gene ontology, the origin of heteroarthrocarpy may still be explained by deviation in expression patterns of one or more of the valve margin pathway genes [18,2226].…”
Section: Discussionmentioning
confidence: 99%
“…Because dehiscence is susceptible to misexpression and loss of function mutations in the valve margin pathway (21,2428), broad changes in gene ontology are unnecessary to explain heteroarthrocarpy. Additionally, GO analyses of top terms do not usually vary between closely related species (65,66). However, similarities in gene ontology do not imply similarity between all expressed transcripts, so variation of just a few transcripts may still be the driving factor behind heteroarthrocarpy.…”
Section: Discussionmentioning
confidence: 99%